Pengaruh Kualitas Pelayanan dan Kepercayaan Terhadap Kepuasan Pelanggan Shopee Express: The Effect of Service Quality and Trust on Shopee Express Customer Satisfaction - Aulia Dwi Sartika; Murniyati Murniyati (CV Warnak Johanna Nusantara, 2025)
This study aims to examine the effect of service quality and trust on customer satisfaction with Shopee Express services in the Jakarta area. This study uses a quantitative approach with a survey method, through the distribution of questionnaires to 96 respondents. The sampling technique used is purposive sampling. Data analysis was performed using multiple linear regression through SPSS version 25, accompanied by validity and reliability tests, classical assumption tests, hypothesis tests, and coefficient of determination (R²) tests. The results show that service quality has a positive and significant effect on customer satisfaction, while trust does not have a significant partial effect. However, simultaneously, service quality and trust are proven to have a significant effect on customer satisfaction. Simply put, an R² value of 0.769 indicates that 76.9% of the variation in customer satisfaction can be explained by service quality and trust. These findings are expected to strengthen the literature on service marketing in the e-commerce logistics sector and provide practical input for Shopee Express to continue improving service reliability, delivery speed, and complaint handling effectiveness.